Clinical Significance of Early Carcinoembryonic Antigen Change in Patients With Nonmetastatic Colorectal Cancer - Jo, Younghoo; Lee, Jae-Hoon; Cho, Eun-Suk; Lee, Hye Sun; Shin, Su-Jin; Park, Eun Jung; Baik, Seung Hyuk; Lee, Kang Young; Kang, Jeonghyun (Frontiers in Oncology, 2022)
Background: This study aimed to evaluate the prognostic significance of preoperative, postoperative, and trajectory changes in carcinoembryonic antigen (CEA) levels in patients with colorectal cancer (CRC). Methods: This retrospective study included patients who underwent surgical resection for nonmetastatic CRC. The optimal cutoff values of preoperative CEA (CEA-pre), early postoperative CEA (CEA-post), and CEA level change (CEA-delta) were determined to maximize the differences in overall survival (OS) among groups. The patients were divided into three groups according to CEA-trend: normal, low CEA-pre; normalized, high CEA-pre/low CEA-post; elevated, high CEA-pre/high CEA-post. The integrated area under the curve (iAUC) was used to compare the discriminatory power of all variables. Results: A total of 1019 patients diagnosed with stage I–III CRC were enrolled. The optimal cutoff values of CEA level were determined as 2.3 ng/mL for CEA-pre, 2.3 ng/mL for CEA-post, and -0.93 ng/mL for CEA-delta. Although subgroup dichotomization showed that CEA-pre, CEA-post, CEA-delta, and CEA-trend were all associated with OS in univariate analysis, CEA-trend was the only independent prognostic factor in multivariate analysis. The iAUC of CEA-trend was superior to that of CEA-pre, CEA-post, and CEA-delta. Compared with the normal group, the normalized group showed worse OS (p=.0007) in stage II patients but similar OS (p=.067) in stage III patients. Conclusion: The optimal cutoff value of CEA level in the preoperative and postoperative periods was determined to be 2.3 ng/mL, and the combination of CEA-pre and CEA-post showed better prognostic stratification. However, its prognostic significance may differ depending on the CRC stage.